An observational study of the impact of genetic testing for pain perception in the clinical management of chronic non-cancer pain. (June 2017) - Sharma, Maneesh; Kantorovich, Svetlana; Lee, Chee; Anand, Natasha; Blanchard, John; Fung, Eric T.; Meshkin, Brian; Brenton, Ashley; Richeimer, Steven
Abstract: Objective: Pain levels are a key metric in clinical care. However, the assessment of pain is limited to basic questionnaires and physician interpretation, which yield subjective data. Genetic markers of pain sensitivity, such as single nucleotide polymorphisms in the catechol-O-methyltransferase gene, have been shown to be associated with pain perception and have been used to provide objective information about a patient's pain. The goal of this study was to determine if physician treatment adjustments based on genetic tests of pain perception resulted in improved outcomes for patients. Material and methods: A prospective, longitudinal study was conducted with 134 chronic non-cancer pain patients genotyped for pain perception-related catechol-O-methyltransferase haplotypes. Physicians were provided with patients' results and asked to document 1) their assessment of benefit of the genetic test; 2) treatment changes made based on the genetic test; and 3) patient clinical responses to changes implemented. Results: Based on genetic testing results, physicians adjusted treatment plans for 40% of patients. When medication changes were made based on genetic testing results, 72% of patients showed improvement in clinical status. When non-pharmacological actions were performed, 69% of physicians felt their patients' clinical status improved. Moreover, physicians believed the genetic test results were consistent with patient pain levels in 85% of cases. Conclusions: These results demonstrate that providing personalized medicine with genetic information related to pain perception affected physician clinical decision-making for a substantial proportion of patients in this study, and that the availability and utilization of this information was a contributing factor in clinical improvement.